Teologi Kontekstual dalam Budaya Simalungun: Analisis Pemanfaatan Ajaran Kristen dalam GKPS, 1963-2003 - Sipayung, Jhon Winley; Sulistiyono, Singgih Tri; Rinardi, Haryono (Badan Riset dan Inovasi Nasional (BRIN), 2025)
This study examines the importance of faith in God as the creator and preserver of culture, critical evaluation of destructive forces in culture, cultural restoration and preservation revial of excellent, cultural accomplishment. This study will also discuss the background, the role of GKPS in the transformation of local Simalungun culture and examples of local Simalungun cultural transformation. Simalungun is one of the ethnic groups that fiemy uphold particularly through the concept of ahap hasimalungunan. Ahap hasimalungunan is an important factor in the foundation of GKPS. Protestant Christian doctrices have been present in the Land of Simalungun since the 19th century, yet its part in local culture has not been broadly explored. This study analyzes the transformation of Protestant Christian teachings on local Simalungun culture through the Simalungun Protestant Christian Church (GKPS) in the period 1963-2003. GKPS, which employs local culture as a strategy of evangelism in Simalungun, is significant factor in endeavors to accelerate evangelism in Simalungun. The inception of Protestant Christian theological doctrinesy was begun mode of teaching faith and educating the Simalungun ethnic community in the realm of reforming the worship and educational systems.